Notes from a wayward son : a miscellany - Walker, Andrew, 1945- (James Clarke & Co., 2020)
"This 'miscellany' puts readers around the table with a teacher who has provided the church with wisdom and passion, allowing us to hear an important contribution to the ongoing conversation about the relationship between the gospel and culture. Andrew Walker's 'ecclesial intelligence' and broad interdisciplinary approach to theology and sociology will undoubtedly capture the imagination of many who are curious about the church's mission in the modern West. Notes from a Wayward Son represents a broad sampling of Walker's writings from a distinguished forty-five-year career -- from explorations of Pentecostalism and Charismatic Renewal to Eastern Orthodoxy, C.S. Lewis, and Deep Church; from the impact of modernity on the ecclesia to mission and ecumenism in the West today"--